CONSORTIUM OF WALLACEAN MICROALGAE IN WEST NUSA TENGGARA FOR BIODIESEL PRODUCTION - Suripto Suripto; Lalu Japa (Universitas Mataram, 2018)
Abstract : This study aims to explore the species richness of biodiesel-producing microalgae in the waters of West Nusa Tenggara to develop renewable energy source, environmentally friendly, and not compete in land use with the agricultural sector. MicroalgaÃÂ samples were collected from various waters in West Nusa Tenggara Province using the concentration method. Species determinationÃÂ ÃÂ and data analysis of microalgae was carried out at the Biology Laboratory, University of Mataram to calculate the abundance of each species. The dominant species of biodiesel-producing microalgae were isolated and cultured by a closed culture system method. The oil content of the microalgae biomass produced was extracted byÃÂ a liquid-liquid extraction method using n-hexane as a solvent. The results show that of the 49 species of marine microalgae identified in the waters of West Nusa Tenggara, there are 12 species of microalgae which are biodiesel producers. Of the 30 freshwater microalga species, only 8 species of microalgae are producers of biodiesel. The microalgae community of marine waters of West Nusa Tenggara is dominated by Bacteriastrumdelicatulum, B. variance, Chaetocerosaffinis, C. liciniosum, C. lorenzianum, Gyrosigma sp., Oscillatoria sp., Pseudonitzschia spp., and Thalassionemanitzschicoides, while freshwater microalgae communities are dominated by Microcystis aeruginosa, M. incerta, Nostoc sp., Pediastrumboryanum, and Staurastumcristatum. The dominant types of biodiesel-producing microalgae isolated and cultured are Chaetocerosamini, Nannochloropsisoculata and Nitzschia spp. Each cell density of C. amini, N. oculata, and Nitzschiaspp in culture 7 days after isolation was 3,600,960,000,ÃÂ 4,375,360,000, andÃÂ 3,368,640,000 cells / liter respectivelyÃÂ with oil content 34, 68, and 46%. Key words: biodiesel, microalgae, Wallacea, West Nusa Tenggara